Cash Waqf: Historical Evolution, Nature and Role as an Alternative to Riba-Based Financing for the Grass Root - Ahmad, Mahadi (Journal of Islamic Finance, 2015)
It is a settled matter among the Muslim jurists that riba in its any form is prohibited. It is so due to the exploitation and injustice associated with riba-based loans. To overcome the resulting hardship of non-availability of easy loans, sustainable alternatives are provided under the Shariah to enhance mutual dealings and promote commercial transactions. This paper sets to explore the Islamic heritage of cash waqf as alternative to riba based financing, the nature and its potentials in assisting the grass root in the society. This is because entrepreneurship which could be one of the key solutions to the growing poverty in the world, availability of cash is a prerequisite to making its wide practice a possibility. It is undisputable that the poor are unbankable and so they are denied access to commercial loans. This research contends that cash waqf could serve as a solution to this problem, by investigating the historical evolution and identifying the challenges that could stand against its development through lessons from the past. The paper finds that cash waqf is capable of promoting entrepreneurship in the world with interest free loans from the cash waqf institutions, making the poor self reliant and dignified.